2021
DOI: 10.1186/s13643-020-01563-8
|View full text |Cite
|
Sign up to set email alerts
|

The scope and nature of sexual orientation and gender identity and expression change efforts: a systematic review protocol

Abstract: Background Sexual orientation and gender identity and expression change efforts (SOGIECE) are a set of scientifically discredited practices that aim to deny and suppress the sexual orientations, gender identities, and/or gender expressions of sexual and gender minorities (SGM). SOGIECE are associated with significant adverse health and social outcomes. SOGIECE continue to be practiced around the world, despite denouncements from professional bodies and survivors, as well as calls for legislativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Aside from emotional abuse, GICP could encompass rejection based on gender identity and produce internalized stigma, all risks that are strongly associated with suicidality 26 . Conversion therapy was also associated with poor self-esteem, internalized stigma and discrimination 5,6,14,20 . In our current findings, regarding TNG individuals who reported GICP, higher self-esteem was shown to be a protective factor for the three primary outcomes (mental health, suicidality and NSSI), while fear of GICP was shown to be the risk factor for the three primary outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from emotional abuse, GICP could encompass rejection based on gender identity and produce internalized stigma, all risks that are strongly associated with suicidality 26 . Conversion therapy was also associated with poor self-esteem, internalized stigma and discrimination 5,6,14,20 . In our current findings, regarding TNG individuals who reported GICP, higher self-esteem was shown to be a protective factor for the three primary outcomes (mental health, suicidality and NSSI), while fear of GICP was shown to be the risk factor for the three primary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…between mental health concerns and conversion therapy 4,5 , and the mental health aftermath is often associated with an elevated rate of selfharm, suicidality, depression and anxiety 6,7 . However, most studies in the literature have focused on the relationship between sexual minority groups and sexual orientation change efforts [8][9][10][11] , and insufficient studies have focused on the influence of gender identity conversion efforts (GICE) on TNG individuals 7 .…”
Section: Description Of Gicpmentioning
confidence: 99%
“…Sexual orientation and gender identity change efforts (SOGICE) (also called conversion therapy ) are dangerous, discredited practices rooted in false beliefs that being lesbian, gay, bisexual, transgender, queer, or questioning (LGBTQ) is pathologic . Based on evidence that SOGICE is ineffective and detrimental, the American Academy of Pediatrics, the American Academy of Child and Adolescent Psychiatry, and other medical, mental health, and human rights organizations formally oppose it …”
Section: Introductionmentioning
confidence: 99%
“…exual orientation and gender identity change efforts (SOGICE) (also called conversion therapy) are dangerous, discredited practices rooted in false beliefs that being lesbian, gay, bisexual, transgender, queer, or questioning (LGBTQ) is pathologic. 1 Based on evidence that SOGICE is ineffective and detrimental, 2 the American Academy of Pediatrics, the American Academy of Child and Adolescent Psychiatry, and other medical, mental health, and human rights organizations formally oppose it. [3][4][5][6][7][8][9][10] Minority stress theory contends that disproportionate rates of health issues among LGBTQ individuals stem from chronic stress and mental health detriments caused by increased exposure to social bigotry and rejection.…”
mentioning
confidence: 99%
“…Moreover, the Human Rights Campaign (n.d.) reported that "conversion" therapies or "reparative" therapies are targeted toward lesbian, gay, bisexual, transgender, and queer youth and are practices that seek to change their sexual or gender identities to fit within a heteronormative and gender normative status quo. In addition, in a recent systematic review, Kinitz et al (2021) defined sexual orientation and gender identity and expression change efforts (SOGIECE) as a "set of scientifically discredited practices that aim to deny and suppress the sexual orientations, gender identities, and/or gender expressions of sexual and gender minorities" (p. 1). As summarized in this 2021 publication, persons who were assigned male at birth to override any feelings of having a more female or effeminate gender identity or expression to take on identities that are more aligned with their gender assigned at birth-that is, to take on identities as more masculine men.…”
mentioning
confidence: 99%